Simian virus 40 small-t antigen stimulates viral DNA replication in permissive monkey cells. - Cicala, C (1994)
The simian virus 40 (SV40) large-T antigen is essential for SV40 DNA replication and for late viral gene expression, but the role of the SV40 small-t antigen in these processes is still unclear. We have previously demonstrated that small t inhibits SV40 DNA replication in vitro. In this study, we investigated the effect of small t on SV40 replication in cultured cells. CV1 monkey cell infection experiments indicated that mutant viruses that lack small t replicate less efficiently than the wild-type virus. We next microinjected CV1 cells with SV40 DNA with and without purified small-t protein and analyzed viral DNA replication efficiency by Southern blotting. Replication of either wild-type SV40 or small-t deletion mutant DNA was increased three- to fivefold in cells coinjected with purified small t. Thus, in contrast to our in vitro observation, small t stimulated viral DNA replication in vivo. This result suggests that small t has cellular effects that are not detectable in a reconstituted in vitro replication system. We also found that small t stimulated progression of permissive monkey cells--but not of nonpermissive rodent cells--from G0-G1 to the S phase of the cell cycle, possibly leading to an optimal intracellular environment for viral replication.